Optimization of Water-in-Biodiesel Emulsification of Palm Oil by Ultrasonic Method using Respons Surface Methodology - Fauzi, Dinda Adelia; Kusumaningtyas, Ratna Dewi; Widyastuti, Catur Rini; Veny, Harumi (Universitas Negeri Semarang, 2025)
Palm oil biodiesel offers a renewable alternative but has high viscosity and density. Emulsifying biodiesel with water reduces these drawbacks and lowers nitrogen oxide (NOx) emissions. This study aims to optimize the emulsification process of water-in-biodiesel emulsion made from palm biodiesel (B100) using an indirect ultrasonic method and the response surface methodology approach with a Box-Behnken design. Three main independent variables were examined: hydrophilic-lipophilic balance values (6, 7.5, and 9), water concentrations (9%, 12%, and 15% v/v), and surfactant concentrations (5%, 7%, and 9% v/v) with a combination of Tween 80 and Span 80 as surfactants. The experimental process involves the synthesis of biodiesel from palm oil through transesterification with the help of 100W ultrasonic power for 15 minutes at room temperature. The analysis was carried out on three main parameters: density, viscosity, and water droplet size on water-in-biodiesel. The results of laboratory tests and statistical modeling show the three independent variables have a significant effect on the physical properties of water-in-biodiesel. The optimization resulted in the best conditions at a hydrophilic-lipophilic balance value of 6.11, water concentration of 9.06%, and surfactant concentration of 5%, with density characteristics of 859.95 kg/m³, kinematic viscosity of 4.44 mm²/s, and average water particle size of 4.46 μm, values close to conventional diesel fuel standards. This study confirms that the indirect ultrasonic method and respons surface methodology-based optimization are effective in improving the performance and character of water-in-biodiesel, potentially becoming a reference for the development of environmentally friendly renewable energy based on palm oil.